Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil - Colpani, Daniara; Benetti, Cesar João; Hamada, Neusa (Zootaxa, 2019)
Gyrinus rhyssonotum sp. n. is described and illustrated based on adult males and females collected in Barcelos County, Amazonas state, Brazil. The new species belongs to the subgenus Oreogyrinus Ochs, 1935 and it is compared with Gyrinus (Oreogyrinus) fittkaui Ochs, 1963 and G. (O.) opalinus Régimbart, 1883, both occurring in the Brazilian Amazonas and G. (O.) colombicus Régimbart, 1883 and G. (O.) venezolensis Ochs, 1954, these two latter alien to the Brazilian fauna but with which G. (O) rhyssonotum sp. n. seems to be more closely related, though the new species can be distinguished from both by a series of characteristics, mainly observed in the body shape, elytra, pronotum, and in male and female genitalia.